Yield gap analysis between irrigated and rainfed rice agroecosystem - Handoko, Handoko; Kurniasih, Budiastuti; Taryono, Taryono (Jurnal Ilmu Pertanian, 2025)
Rice is an essential crop for worldwide food security, providing the primary feeding for nearly half of the people on earth. In order to meet the increasing demand for rice, it is necessary to reduce the yield gap between irrigated and rainfed rice agroecosystem; therefore, a descriptive approach is used to estimate the yield gap (Yg) between irrigated (Yp) and rainfed rice agroecosystems (Yw) and identify its key factors. This research aimed to identify the causes of the yield gap between irrigated and rainfed rice agroecosystems and evaluate the causes of the yield gap so as to minimize the yield gap. This research had been conducted from December 2021 to April 2022 in two different locations, an irrigated and a rainfed rice agroecosystem (planted between M. cajuputi stands). Fourteen genotypes were grown in a complete randomized block design consisting of three blocks in each location (irrigated and rainfed rice fields). The experimental unit at each research location was 20 m² (4 m × 5 m), and the harvest area was 12 m² (3 m × 4 m), consisting of 192 populations of rice plants. The results showed that soil fertility limiting factors, including total nitrogen, phosphorus and available potassium caused the yield gap. The maximum yield recorded was in G2 (8.83 ton.ha⁻¹) in the irrigated agroecosystem, while the minimum yield was in G8 (0.64 ton.ha⁻¹) in the rainfed agroecosystem. Yield gap analysis revealed a gap of 5.27 ton.ha⁻¹ between the irrigated and rainfed systems. The most significant yield gap was observed in G3 at (6.92 ton.ha⁻¹), whereas the least was in G10 (3.17 ton.ha⁻¹). The genotype G2, exhibiting the highest yield in the irrigated agroecosystem, is recommended for planting, while G4, with a potential yield of 4.14 ton.ha⁻¹, is suggested for rainfed agroecosystems.